National planetary health learning objectives for Germany: a steppingstone for medical education to promote transformative change - Wabnitz, Katharina; Schwienhorst-Stich, Eva-Maria; Asbeck, Franziska; Fellmann, Cara Sophie; Gepp, Sophie; Leberl, Jana; Mezger, Nikolaus Christian Simon; Eichinger, Michael (Frontiers in Public Health, 2023)
Climate change, curriculum development, education for sustainable healthcare, medical education, Planetary Health, Planetary Health Education, transformative education
Gesehen am 19.05.2023